Domains and indicators of consumer legal literacy in Malaysia - Samsudin, Norhafifah; Abu Bakar, Elistina; Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura; Sulaiman, Norhasmah (Universiti Putra Malaysia Press, 2018)
Legal literacy is one of the important aspects of consumer empowerment. The objective of this paper is to determine the domains and indicators of legal literacy in Malaysia. The methodologies used are a combination of qualitative and quantitative research. The qualitative method utilised a Focus Group Discussion (FGD) technique, while the data for quantitative method were gathered through a survey. The findings of the FGD reveal that there are eight domains of consumer legal literacy that are based on consumer rights. The rights are the right to basic needs, the right to safe goods and services, the right to information, the right to make a choice, the right to be heard, the right to get compensation, the right to consumer education and the right to life in a healthy and safe environment. However, the results of the factor analysis revealed five domains, which are the right to safe and quality goods and services, the right to compensation, the right to consumer education, the right to be informed of financial matters and the right to be heard and to obtain information. Altogether, there are 46 indicators for measuring consumer legal literacy. The domains and indicators can be used to develop a Malaysian Legal Literacy Index and provide the instruments for measuring legal literacy in Malaysia.